2017
DOI: 10.1155/2017/5308635
|View full text |Cite
|
Sign up to set email alerts
|

Review of Factors Related to the Thyroid Cancer Epidemic

Abstract: Thyroid cancer is the most common endocrine cancer, of which the incidence has dramatically increased worldwide in the past few decades. The reasons for the observed rapid increase still are not fully understood, but evidence suggests that overdiagnosis, with the advancement in detection methods and screening policies, is not the sole driver of the substantial increase of the incidence. However, the effect of environmental/lifestyle factors remains speculative other than that of radiation exposure at a young a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 103 publications
0
76
1
4
Order By: Relevance
“…Studies examining etiological factors associated with thyroid cancer have generally focused on adult thyroid cancers. 19 Large epidemiological studies of DTC risk factors among children are needed to provide insight into etiology. However, known risk factors for thyroid carcinogenesis among adults may also be associated with childhood DTC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining etiological factors associated with thyroid cancer have generally focused on adult thyroid cancers. 19 Large epidemiological studies of DTC risk factors among children are needed to provide insight into etiology. However, known risk factors for thyroid carcinogenesis among adults may also be associated with childhood DTC.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is mainly related to the growing incidence of papillary TC (PTC) [ 8 ]. It is still the matter of debate whether it is a consequence of improved diagnostic methods and screening or represents a real change in TC incidence due to some environmental factors [ 9 , 10 , 11 ]. It is very probable that more accurate and easy accessible imaging examinations result in a better detection of thyroid tumors.…”
Section: Follicular-cell Derived Thyroid Cancersmentioning
confidence: 99%
“…An analysis based on SEER data including the years between 1998 and 2010 revealed that 5- and 10-year survival of patients who underwent total thyroidectomy for papillary microcarcinoma (PTMC) was similar to that of a general population [ 15 ]. Moreover, an increasing number of ITNs was classified as “follicular variant of PTC” (FVPTC) rather than follicular adenomas (FA) [ 11 ], which in consequence could be responsible for the number of overdiagnosed and ovetreated TC cases. This has been changed since the reclassification of encapsulated noninvasive follicular variants of PTC as a benign lesion, currently renamed as “noninvasive follicular thyroid neoplasm with papillary like nuclear features” (NIFTP) [ 16 ].…”
Section: Follicular-cell Derived Thyroid Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…While ultrasonographic characteristics and fine-needle aspiration (FNA) are the sine qua non of thyroid nodule investigation, papillary thyroid microcarcinomas (PTMC, tumours ≤1 cm along their largest diameter by the WHO definition) not infrequently escape preoperative diagnosis and are only revealed in the final histology report [ 1 ]. These occult papillary microcarcinomas constitute the majority of incidentally discovered thyroid malignancies in patients undergoing surgery for presumably benign disease, with a reported incidence of up to 15% [ 1 ]. Although they generally carry excellent prognosis, a small percentage represents aggressive tumours with unfavourable patient outcomes [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%